Inductive Argument as a Check upon Growing Knowledge - Skersytė, Jūratė (Problemos, 1975)
The aim of the article is to explain the functions of induction in the process of cognition. Special attention is given to such aspects of the Marxist methodology which determine the new posing of the so-called problem of induction. The author criticizes the widespread tendency (both in the Soviet and foreign literature) to pose the problem of induction as one of the possibility of knowing the world. The author tries to show that from the view-point of the social practical determination of cognition scientific progress does not consist in the transfer from the particular to the general but rather from the general to the general, the individual experience being but the functionally dependent mediator. Therefore two aspects should be distinguished in the problem of generalization: 1) the general-methodological, and 2) the formal-logical. The conclusion is made that the conception of the inductive argument has come historically and is developing as a special theory of the structure of generalization. The generalization itself is not genetically connected with observation of recurrence and functions independently of the conception of induction.